Future Security 7th Security Research Conference, Future Security 2012, Bonn, Germany, September 4-6, 2012. Proceedings - Aschenbruck, Nils (Communications in Computer and Information Science, 2012)
This book constitutes the refereed proceedings of the 7th Security Research Conference, Future Security 2012, held in Bonn, Germany, in September 2012. The 78 revised full papers presented were carefully reviewed and selected from 137 submissions. The papers are organized in topical sections on supply chain and critical infrastructure protection; security situational awareness; crisis management; security for critical infrastructure and urban areas; sensor technology; social, psychological and political aspects; cyber defense and information security; maritime and border security; detection of hazardous materials; food chain security; aviation security; ergonomic aspects.